TRANSFORMASI POLIGAMI DALAM BINGKAI SYARI’AH ISLAM DI ACEH - Muhammad Zukhdi; Faisal Faisal (Universitas Islam Negeri Sumatera Utara, 2020)
People’s views on polygamy are diverse, there are those who agree, but there are also those who disagree or oppose even more for women who feel disadvantaged, because they have to share with others. This is influenced by the family economy which does not allow polygamy. Such allegations eventually feel unsatisfied with suspection and even challenge qath’i syar’i texts with interpretations that are far from the elements of truth. So that legal issues are interpreted with multiple interpretations and cause vague and vague issues. And the Aceh which was given the authority in making qanun implementation of islamic shari’ah and participated in discussing anddesigning the Qanun (Raqan) family law which regulates polygamy but the draft qanun raises pro and contra at the people of Aceh.